First Principles Study of Electronic Band Structure and Structural Stability of Al2C Monolayer and Nanotubes - S. Pramchu (2018)
© Published under licence by IOP Publishing Ltd. We used density functional theory (DFT) based on generalized gradient approximation (GGA) and hybrid functional (HSE06) to investigate band gap and structural stability of Al 2 C monolayer and nanotubes. From the results, both GGA and HSE06 band gaps of Al 2 C monolayer agree well with previously reported data. For the Al 2 C nanotubes, we found that their band gaps are more sensitive to the size and the chirality than that of the widely studied SiC 2 nanotubes, indicating the Al 2 C nanotubes may have higher band gap tuning capabilities (with varying diameter size and chirality) compared with those of SiC 2 nanotubes. We have also discovered a desirable direct band gap in the case of (n,0) nanotubes, although Al 2 C monolayer band gap is indirect. The calculated strain energy reveals that (n,0) nanotubes constructed by wrapping up Al 2 C monolayer consume less energy than (0,n) nanotubes. Thus, (n,0) nanotubes is easier to synthesize than (0,n) nanotubes. This discovery of direct band gap in (n,0) Al 2 C nanotubes and their adjustable band gap suggests them as promising sensitizer for enhancing power conversion efficiency of excitonic solar cells.